Uranium-mediated reductive conversion of CO2 to CO and carbonate in a single-vessel, closed synthetic cycle - Schmidt, Anna-Corina; Nizovtsev, Alexey; Scheurer, Andreas; Heinemann, Frank Wilhelm; Meyer, Karsten (Chemical Communications, 2012)
The new neopentyl (Neop)-substituted tris(aryloxide) U(iii) complex [((ArO)tacn)U] reacts with CO to form CO and the bridging carbonate complex [(( ArO)tacn)U(μ-CO )]. The uranium(iv) bridging oxo [((ArO) tacn)U(μ-O)] has been determined to be the intermediate in this reaction. For the first time, both U(iv) complexes can be reduced back to the U(iii) starting material. Thus, with KC as reductant, [((ArO)tacn)U] engages in a synthetic cycle, in which CO is converted to CO and CO . © 2012 The Royal Society of Chemistry.